Socialism from the early premises of thought to the experiments of ages: A study of the intellectual roots and historical transformations of the socialist system - Abid, Sabah; Rabehi, Mohammed; Moussaoui, Youcef (The International tax journal, 2025)
This study aims to trace the historical trajectory of socialism from its earliest emergence as a philosophical idea rooted in class struggle to its practical experiments in the modern era. The rise of socialism in Europe was closely linked to the intellectual and practical responses to the Napoleonic Wars, the Industrial Revolution, and the revival of democratic values during the eighteenth and nineteenth centuries. It was further deepened by the contributions of Karl Marx, who transformed socialism from a critical theory into a societal project with political and economic dimensions. The research also examines the intersection between socialism and nationalist movements, highlighting the attempts of early pioneers such as François-Noël Babeuf and Philippe Buonarroti to revive the Constitution of 1793, which promised greater social equality. This trajectory was later embodied in major experiments in the Soviet Union, Eastern Europe, China, Vietnam, Cuba, and North Korea, where socialism faced challenges such as centralized planning, resource management, and the reduction of class disparities. Through this comparative historical reading, the study seeks to demonstrate how socialism has constituted a distinctive model in its pursuit of social justice and how its legacy continues to shape contemporary political and economic systems.